Analisis Pengukuran Produktivitas di PT. Preshion Engineering Plastec Surabaya dengan Metode OMAX (Objective Matrix) - Putri Wulan Cahyani; Ni Luh Putu Hariastuti (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2022)
Nowadays, competition between companies is unavoidable. A company has a specific strategy in order to survive and increase their respective advantages. PT. Preshion Engineering Plastec is a foreign-owned company active in the manufacturing industry. Not infrequently in the production process there are several obstacles such as not being able to meet targets, less than optimal employee performance to productivity problems. With that, it is necessary to measure productivity which aims to determine the level of productivity, the factors that cause productivity to decline to find solutions to various kinds of problems. That way, researchers try to solve various kinds of problems using the Objective Matrix (OMAX) method. The results of the calculation of productivity using the OMAX method obtained the best productivity of 726,88, the index of change to the previous productivity of +310,01% and the index of change to the standard productivity of +43,08%.